Boat landing at Atlin, Atlin Lake, British Columbia, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Sign on dock reads: "John Irving Navigation Co. Steamers Scotia and Gleaner for Bennett". Mt. Atlin in background. Caption on image: "Mt. Atlin. Atlin Lake and boat landing at Atlin B.C." Original image in Hegg Album 9, page 22. Klondike Gold Rush.